Performance characteristics of a compact core annular-radial magnetorheological damper for vehicle suspension systems - Ahmad Zaifazlin, Zainordin; Zamri, Mohamed (Universiti Malaysia Pahang, 2024)
The magnetorheological (MR) damper is a by-wire system capable of providing variable damping stiffness by responding to an apparent magnetic field. In response to the magnetic field application, the magnetorheological fluid (MR fluid) exhibited altered behavior within the damper. Typically, a damper’s internal and external valves operate in flow mode, where the flow is regulated by controlling the magnetic field. This study aims to investigate the performance characteristics of a small core annular and radial magnetorheological valve (SCARMV) designed for applications in vehicle suspension systems. The proposed design of the simplified MR valve is based on a meandering-type valve composed of multiple valve cores that have been simplified to a single core. Dynamic testing was performed on the proposed valve, which features a single rod tube damper, to investigate the damping force characteristics by varying currents and frequencies. The characteristics of the measured damping force were compared to the calculated damping force based on the pressure drop calculation and the FEMM simulation of magnetic flux. By increasing the stroke length of the valve travel is set to 10 mm at a current input of 0 A to 1.0 A, the maximum output of the MR valve damping force was approximately 1.57 kN. In addition, a mathematical model of SCARMV is presented and compared to the experimental data. Therefore, based on the experimental results, it was concluded that the usability of a compact core MR valve is reliable. However, more in-depth studies are required before these dampers can be applied to vehicle suspension systems.